Designing the user experience of a spatiotemporal automated home heating system: a holistic design and implementation process - Kruusimagi, Martin (2017)
This research explores technological interventions to reduce energy use in the domestic sector, a notable contributor to the global energy footprint. In the UK elevated challenges associated with renovating an outdated, poorly performing housing stock render a search for alternatives to provide immediate energy saving at low cost. To solve this problem, this thesis takes a holistic design approach to designing and implementing a spatiotemporal heating solution, and aims to investigate experiences of comfort, thermal comfort concepts for automated home heating, users’ interactions and experiences of living with such a system in context, and the underlying utility of quasi-autonomous spatiotemporal home heating.